Kemampuan Mendesain Media Pembelajaran Menggunakan Software Aplikasi Visual Basic Macro dengan Model Kooperatif Jigsaw Berbasis Weblog - Wardani, Theodora Indriati; Purwosetiyono, FX Didik; Riyanto, Riyanto (Universitas PGRI Semarang, 2024)
Digital simulation courses consist of theory and practice must master theory first before they practice. Theory obtained by students from lectures equipped with webblog-based books / diktats about learning media design. In the visual basic macro software application there are instructions in designing learning media. So, to design learning media using visual basic macro software applications, students must be able to understand visual basic macro software applications. By understanding the procedure for designing learning media, it is hoped that students can practice designing learning media using visual basic macro software applications to produce something whose printout is in the form of text and images. The problem being studied is which learning model is more effective between the cooperative model of the Jigsaw model and the conventional model. The problem being studied is which learning model is more effective between the cooperative model of the Jigsaw model and the conventional model. To solve this problem, experimental research was carried out at PGRI Semarang University, especially students majoring in S1 Information Technology Education, Faculty of PMIPATI semester 6 who were taking the Digital Simulation course. They have 1 class, each class averages 15 students. For the target of this study were taken 15 people, so their number was 30 people. In this study there are 2 types of data, namely: (1) Jigsaw cooperative model group data on the ability to design learning media using visual basic macro software applications with grouping treatment, and (2) conventional model group data without grouping treatment on the ability to design learning media using Visual Basic Macro software applications. Data from the Jigsaw model cooperative group as well as conventional models on the ability to design learning media using visual basic macro software applications were obtained with tasks. The data were statistically calculated with a t-test to determine the effectiveness comparison between the Jigsaw cooperative model group and the conventional model. The data were statistically calculated with a t-test to determine the effectiveness comparison between the Jigsaw cooperative model group and the conventional model. The results of this t test show that the Jigsaw cooperative model using grouping shows that the ability to design learning media using visual basic macro software applications is more effective than conventional models without using grouping treatment.